1999
DOI: 10.1128/mcb.19.1.594
|View full text |Cite|
|
Sign up to set email alerts
|

The Oncogenic Potential of the Pax3-FKHR Fusion Protein Requires the Pax3 Homeodomain Recognition Helix but Not the Pax3 Paired-Box DNA Binding Domain

Abstract: The chimeric transcription factor Pax3-FKHR, produced by the t(2;13)(q35;q14) chromosomal translocation in alveolar rhabdomyosarcoma, consists of the two Pax3 DNA binding domains (paired box and homeodomain) fused to the C-terminal forkhead (FKHR) sequences that contain a potent transcriptional activation domain. To determine which of these domains are required for cellular transformation, Pax3, Pax3-FKHR, and selected mutants were retrovirally expressed in NIH 3T3 cells and evaluated for their capacity to pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
76
0

Year Published

1999
1999
2011
2011

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(81 citation statements)
references
References 33 publications
5
76
0
Order By: Relevance
“…First, it might explain the failure of Pax5 to activate the Bcl-x promoter, since Pax5 contains only a partial homeobox (Adams et al, 1992). Second, it has recently been suggested that the oncogenic potential of PAX3/FKHR requires the homeodomain, but not the paired box domain (Lam et al, 1999). It might be interesting to see whether other PAX proteins containing a complete homeodomain (PAX7, PAX4 and PAX6) can bind to and activate the Bcl-x promoter.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…First, it might explain the failure of Pax5 to activate the Bcl-x promoter, since Pax5 contains only a partial homeobox (Adams et al, 1992). Second, it has recently been suggested that the oncogenic potential of PAX3/FKHR requires the homeodomain, but not the paired box domain (Lam et al, 1999). It might be interesting to see whether other PAX proteins containing a complete homeodomain (PAX7, PAX4 and PAX6) can bind to and activate the Bcl-x promoter.…”
Section: Discussionmentioning
confidence: 99%
“…The PAX3/FKHR fusion protein then, was demonstrated to transform mouse (Lam et al, 1999) and chicken ®broblast cells in culture (Scheidler et al, 1996) upon ectopic expression. On the molecular level, the exchange of the PAX3 transactivation domain with that of the FKHR protein renders the fusion protein a more potent transactivator which retains the DNA binding properties of PAX3.…”
Section: Introductionmentioning
confidence: 99%
“…The PAX3-FKHR chimera is a more potent transcriptional activator than wild type pax3 (Fredericks et al, 1995), and presumably disrupts the normal regulation of target genes downstream of PAX3. Recently, it was reported that it is the PAX3 homeodomain recognition helix, and not the pairedbox DNA binding domain, that is required for transformation by the PAX3-FKHR chimera (Lam et al, 1999). The involvement of PAX3 in RMS is strongly reinforced by its demonstrated role in skeletal muscle development, as discussed below.…”
Section: Cytogenetic De®nition Of Rhabdomyosarcomamentioning
confidence: 97%
“…A precedent for such complexity in transformation by chimeric transcription factors was demonstrated in studies of three tumor-associated fusion proteins: E2A/PBX1 derived from pre-B cell lymphoblastic leukemia, PAX3/FKHR found in alveolar rhabdomyosarcoma, and E2A/HLF found in pro-Bcell acute lymphoblastic leukemia. Mutational analyses of these fusion proteins showed that while transforma- (Lam et al, 1999;Muller et al, 1991). Transformation assays were carried out as described by May et al (1993a) with the following minor modi®cations.…”
mentioning
confidence: 99%
“…Colonies were scored 3 weeks post-plating. Assays were repeated seven times for vector, EWS/FLI, and EWS/FLI I347E, and repeated four times for EWS/FLI W321R, EWS/FLI R337, 340L and EWS/FLI del54 tion did not require DNA-binding, the ability to interact with other proteins was required (Chang et al, 1997;Inukai et al, 1998;Lam et al, 1999). The lack of transforming activity of EWS/FLI W321R and R337, 340L indicates that these mutations may disrupt more than DNA binding activity.…”
mentioning
confidence: 99%